2021
DOI: 10.1007/s10877-021-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure-controlled ventilation-volume guaranteed mode combined with individualized positive end-expiratory pressure on respiratory mechanics, oxygenation and lung injury in patients undergoing laparoscopic surgery in Trendelenburg position

Abstract: The study aimed to investigate the efficacy of PCV-VG combined with individual PEEP during laparoscopic surgery in the Trendelenburg position. 120 patients were randomly divided into four groups: VF group (VCV plus 5cmH2O PEEP), PF group (PCV-VG plus 5cmH2O PEEP), VI group (VCV plus individual PEEP), and PI group (PCV-VG plus individual PEEP). Pmean, Ppeak, Cdyn, PaO2/FiO2, VD/VT, A-aDO2 and Qs/Qt were recorded at T1 (15 min after the induction of anesthesia), T2 (60 min after pneumoperitoneum), and T3 (5 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…PCV allows the ventilator to maintain pressure at the airway opening for a specified period of time (14)(15)(16)(17). As such, the final tidal volume and flow rate are affected by compliance, airway resistance, and spontaneous breathing.…”
Section: Discussionmentioning
confidence: 99%
“…PCV allows the ventilator to maintain pressure at the airway opening for a specified period of time (14)(15)(16)(17). As such, the final tidal volume and flow rate are affected by compliance, airway resistance, and spontaneous breathing.…”
Section: Discussionmentioning
confidence: 99%
“…However, applying a low V T with a fixed or insufficient PEEP for all patients is inappropriate because this may lead to atelectrauma [32]. Our team found that employing individualized PEEP can improve oxygenation and reduce inflammatory markers compared with fixed PEEP strategies in patients undergoing thoracoscopic and laparoscopic surgery [11,12]. Hence, we assume that individualized PEEP can prevent POD among elderly surgical patients in prone position by increasing rSO 2 and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative lung-protective ventilation strategies, including low tidal volumes (V T ), PEEP, and recruitment maneuvers (RM), have been proved to alleviate lung injury and prevent POD [4,10]. Our previous studies have shown that individualized PEEP combined with pressure-controlled ventilation-volume guaranteed (PCV-VG) mode could mitigate lung damage, and lead to favorable oxygenation in patients undergoing thoracoscopic surgery and laparoscopic surgery [11,12]. Recent studies demonstrated that the application of PEEP could induce significant increases in rSO 2 [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure‐controlled volume‐guaranteed ventilation (PCV‐VG) is a novel ventilation type, combining the advantages of both volume‐controlled ventilation (VCV) and pressure‐controlled ventilation (PCV) 6 . PCV‐VG automatically adjusts airway pressure according to the mechanical parameters of each breath, which is an important part of the protective ventilation strategy 7 . Numerous studies have shown that positive end‐expiratory pressure (PEEP) increases lung compliance, prevents alveolar collapse, and improves oxygen diffusion, thereby improving pulmonary dynamics and gas exchanges 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal PEEP is determined by “PEEP titration” according to the patient's specific situation, which stabilizes lung function, minimizes lung injury, and achieves lung protection 9 . Optimal PEEP titration determined by lung dynamic compliance (Cdyn) is widely used in clinic practice and has been shown to reduce PPCs in patients undergoing abdominal surgery 7 . Different PEEP titration methods (incremental or decremental) may produce different results with individual PEEP settings; however, the specific differences in their effectiveness are unclear.…”
Section: Introductionmentioning
confidence: 99%